Analisis Perilaku Asuh Makan Usia 24-59 Bulan terhadap Kejadian Stunting di Puskesmas Tanjungrejo Kabupaten Kudus - Naila Ainun Nisa; Novie E. Mauliku; Budiman Budiman; Ayu Laili Rahmiati; Suhat Suhat (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Stunted toddlers at Tanjungrejo Health Center increased 2024 to 259 toddlers, 79 stunted 24-59 months. Study aims analyze relationship parenting patterns and stunting 24-59 months at Tanjungrejo Health Center. Study design used case-control. Sample 50 mothers stunted as cases and 100 mothers healthy children as controls. Ratio 1:2 using simple random sampling. Data collection used questionnaire with univariate, bivariate, and multivariate analysis. Results is significant relationship maternal BMI (p=0.009), maternal anemia history (p=0.018), exclusive breastfeeding (p=0.001), meal frequency (p=0.000), meal duration (p=0.000), personal hygiene (p=0.000), maternal parenting (p=0.030) and toddler eating behavior (p=0.000) with incidence stunting. There no significant relationship maternal nutritional status (p=0.839), birth weight (p=0.756), history infection (p=0.839), and type food (p=0.089) with incidence stunting. Largest proportion stunted male aged 24-41 months and respondents aged <27 years with elementary/junior high school and unemployed compared proportion healthy toddlers. The most dominant factor was meal frequency, while food type and personal hygiene were confounding variables. It is recommended to hold healthy cooking demonstrations to implement meal schedules and develop further research on healthy eating behaviors.